3D printing of magnetic parts by laser powder bed fusion of iron oxide nanoparticle functionalized polyamide powders - Hupfeld, Tim; Salamon, Soma; Landers, Joachim; Sommereyns, Alexander; Donate-Buendia, Carlos; Schmidt, Jochen; Wende, Heiko; Schmidt, Michael; Barcikowski, Stephan; Goekce, Bilal (Journal of Materials Chemistry C, 2020)
The development of new feedstock materials is a central prerequisite for advances in Additive Manufacturing (AM). To increase the breadth of potential applications for 3D and 4D printing of polymers, micro- and nano-additives incorporated into the feedstock material play an important role. In this context, magnetic materials are of great interest. Our study describes a way to fabricate polymer powders for laser powder bed fusion (PBF-LB) with a homogeneous, well-dispersed coating of iron oxide nanoparticles. Without the addition of chemical precursors, spherical superparamagnetic FeO(x)nanoparticles with monomodal size distribution below 10 nm are generated from FeO(x)micropowder by laser fragmentation in liquid. The adsorption of the nanoparticles on polyamide (PA12) powder is conducted directly in an aqueous dispersion after laser fragmentation, followed by drying, powder analysis and PBF-LB processing.ViaMossbauer spectroscopy and magnetometry, we determined that the saturation magnetization and structure of the iron oxide nanoparticles were not influenced by PBF-LB processing, and the magnetic properties were successfully transferred to the final 3D-printed magnetic part.
CRIS-Team WoS Importer:2020-10-02

Analysis of the Nanoparticle Dispersion and Its Effect on the Crystalline Microstructure in Carbon-Additivated PA12 Feedstock Material for Laser Powder Bed Fusion - Hupfeld, Tim; Sommereyns, Alexander; Riahi, Farbod; Donate-Buendia, Carlos; Gann, Stan; Schmidt, Michael; Goekce, Bilal; Barcikowski, Stephan (Materials, 2020)
Driven by the rapid development of additive manufacturing technologies and the trend towards mass customization, the development of new feedstock materials has become a key aspect. Additivation of the feedstock with nanoparticles is a possible route for tailoring the feedstock material to the printing process and to modify the properties of the printed parts. This study demonstrates the colloidal additivation of PA12 powder with laser-synthesized carbon nanoparticles at >95% yield, focusing on the dispersion of the nanoparticles on the polymer microparticle surface at nanoparticle loadings below 0.05 vol%. In addition to the descriptors "wt%" and "vol%", the descriptor "surf%" is discussed for characterizing the quantity and quality of nanoparticle loading based on scanning electron microscopy. The functionalized powders are further characterized by confocal dark field scattering, differential scanning calorimetry, powder rheology measurements (avalanche angle and Hausner ratio), and regarding their processability in laser powder bed fusion (PBF-LB). We find that heterogeneous nucleation is induced even at a nanoparticle loading of just 0.005 vol%. Finally, analysis of the effect of low nanoparticle loadings on the final parts' microstructure by polarization microscopy shows a nanoparticle loading-dependent change of the dimensions of the lamellar microstructures within the printed part.
CRIS-Team WoS Importer:2020-08-28

Biodegradable Polylactide Supraparticle Powders with Functional Additives for Biomedical Additive Manufacturing - Canziani, Herbert; Hanschmann, Benedikt; Tischer, Florentin; Sommereyns, Alexander; Distler, Thomas; Schramm, Jonas; Hesse, Nicolas; Schmidt, Jochen; Grünewald, Alina; Detsch, Rainer; Boccaccini, Aldo R.; Maskos, Michael; et al. (Advanced Functional Materials, 2022)
Additive manufacturing, in particular powder bed-based fabrication processes hold promise to revolutionize biomedical engineering for the ability to provide customized, functional implants, for example as bone replacement materials. However, providing functional powder particles that unify material requirements for biodegradable and bioactive biomaterials and process requirements to enable successful powder bed fusion remains an unmet challenge. Here, a supraparticle-based approach to create biodegradable poly(lactic acid) and composite powders for the additive manufacturing of bone replacement materials is introduced. Colloidal binary Ca-SiO2 glasses and hydroxyapatite are incorporated as bioactive functional additives to support the formation of bone-like calcium phosphate. The supraparticle powders are prepared by a scalable spray-drying process, which offers control of particle size, shape, and composition. All process-relevant powder characteristics are analyzed as a function of composition and structure, including flowability, thermal, and melt rheological properties. The optimized supraparticle powders are successfully used in the process of laser powder bed fusion of polymers to prepare macroscopic specimens via additive manufacturing. It is demonstrated that the material combination of the composites provides relevant functional properties, including biodegradation and bioactivity. The process provides a flexible and adjustable toolbox for the design of functional powders toward biomedical additive manufacturing.<br
Keywords: 3D printing; additive manufacturing; biomaterials; PLA; powder bed fusion; spray drying; supraparticles

Correlation of optical energy onto nano-Additivated CuS/PA12 and LaB6/PA12 powder with depth of fusion in PBF-LB/P - Leupold, Simon; Willeke, Michael; Leong, Cheechau; Stratmann, Nadine; Sommereyns, Alexander; Ziefub, Anna Rosa; Kopp, Sebastian-Paul; Barcikowski, Stephan; Schmidt, Michael (Procedia CIRP, 2024)
The printability in laser powder bed fusion of polymers is significantly depended on the absorption of the laser light and the energy density provided by the laser. Most commonly, a CO2 laser is used for PBF-LB/P requiring no additional absorbers. However, when utilizing near-infrared diode lasers, additional absorbers are needed as the polymers themselves do not absorb enough energy at this wavelength. The interactions of light, polymer and absorbers have yet to be fully understood. In this study, the absorptance and resulting geometry of polyamide 12 coated with CuS and LaB6 nanoparticles, made by high-power laser-fragmentation, were analyzed. Multilayer samples consisting of five layers were manufactured at specific energy densities, using a 808 nm PBF-LB/P diode laser setup, and the resulting dimensions were measured. The results suggest that the nanoparticle intrinsic properties can significantly affect resulting geometrical accuracy, even for small quantities of nanoparticles.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Copper monosulfide nanoparticles; Lanthanum hexaboride nanoparticles; NIR Laser; PA12; PBF-LB/P

Efficiency of single-pulse laser fragmentation of organic nutraceutical dispersions in a circular jet flow-through reactor - Friedenauer, Tina; Spellauge, Maximilian; Sommereyns, Alexander; Labenski, Verena; Esatbeyoglu, Tuba; Rehbock, Christoph; Huber, Heinz P.; Barcikowski, Stephan (Beilstein Journal of Nanotechnology, 2025)
Nutraceuticals provide health benefits and particularly profit from a sensitive, high-purity production process. Microparticle laser fragmentation in liquids is an emerging technique for the contamination-free comminution of organic drugs and nutraceuticals aiming at solubility enhancements. However, current discontinuously operated fragmentation setups suffer from chemical degradation by multipulse laser excitation at high fluence and do not allow for systematic studies of the fragmentation mechanisms. In this work, continuous-flow microparticle laser fragmentation in liquids with ultrashort-pulsed lasers was studied in a circular jet reactor using curcumin and cannabidiol as model substances and single-pulse-per-volume element conditions to compare the fragmentation efficiency for these two nutraceuticals. Fragmentation efficiency based on the yield of submicrometer particles and nanoparticles was quantified using UV–vis extinction spectroscopy, scanning electron microscopy, and analytical centrifugation, while high-performance liquid chromatography determined degradation. We found improved fragmentation efficiency at lower mass concentrations. In all experiments, chemical degradation was minimal (<2%), and increased mass concentration of curcumin enabled ultralow by-product formation of 0.01%. The process selectivity against degradation was defined by the application-relevant descriptor of mole degradation per produced submicrometer particle surface and quantified regarding feedstock mass concentration and nutraceutical type. Cytotoxicity in HepG2 cancer cells was significantly reduced in cells treated with laser-processed curcumin in comparison to unirradiated curcumin controls, and antioxidant effects were proven, ensuring high viability even at high curcumin concentration
Keywords: antioxidant; cannabidiol; curcumin; drug; food additive; low degradation; nanoparticle; pulsed laser ablation in liquids; solubilization

Evaluation of essential powder properties through complementary particle size analysis methods for laser powder bed fusion of polymers - Sommereyns, Alexander; Hupfeld, T.; Gökce, B.; Barcikowski, S.; Schmidt, Michael (Procedia CIRP, 2020)
The resolution of complex parts produced by laser powder bed fusion of polymers (PBF-LB/P) is defined significantly by the shape and size distribution of the feedstock powder. Its analysis is usually performed by optical measurement systems such as laser diffraction or image analysis. In this study, the most relevant particle size parameters will be extracted from a set of different measuring methods, as well as the Hausner ratio and finally discussed regarding safe and successful processability. Extracted data include the sphericity, fine fraction, volume- and number-weighted diameter distributions, and statistical significance analysis, including comparison of PA12 and carbon-black-additivated PA12. The presented results should give researchers a first impression about the suitability of polymer powders for PBF-LB/P, based on powder feedstock characterization.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Flowability; Image analysis; Laser beam melting; Laser diffraction; Particle size distribution; PBF-LB/P; Polymer powders; Selective laser sintering

Experimental, numerical and analytical investigation of the polyamide 12 powder bed fusion with the aim of building dimensionless characteristic numbers - Grünewald, Moritz; Popp, Kevin; Rudloff, Johannes; Lang, Marieluise; Sommereyns, Alexander; Schmidt, Michael; Mohseni-Mofidi, Shoya; Bierwisch, Claas (Materials & Design, 2021)
In powder bed fusion (PBF), a laser based energy source selectively fuses polymer powder particles in a layer-by-layer process building up a three-dimensional structure. For powder bed fusion of polymers the knowledge about which material properties are important for the process and the product quality is insufficient. This causes significant difficulties in developing new materials. To address this problem, it is necessary to establish a clear link between the material properties, process parameters and the resulting component quality. This link can be achieved by performing a combination of experimental investigations, numerical simulations and analytical considerations to develop dimensionless characteristic numbers that are able to describe the process. Therefore, this paper presents material properties and monolayer printing experiments for polyamide 12. The experimental results are compared with numerical simulations based on the material and process data. Based on these results, we present a method of how to calculate the dimensionless energy input by combining the surface energy density with material properties and measured thickness of the monolayer samples. Furthermore, when considering the fusion time, numerical simulations show good correlation with an analytical model
CRIS-Team Scopus Importer:2021-01-29
Keywords: Additive manufacturing; Dimensionless numbers; Melting; Polyamide; Powder bed fusion; Simulation

Functional polyetheretherketone coatings fabricated by laser-based directed energy deposition - Wittmann, Alexander; Alidoust Chamandani, Saeed; Hentschel, Oliver; Sommereyns, Alexander; Kopp, Sebastian-Paul; Schmidt, Michael (Surface & Coatings Technology, 2025)
In this paper, directed energy deposition of polymers (DED-LB/P) with a thulium laser is investigated for the first time to apply functional polyetheretherketone coatings on stainless steel 316L sheets. Powder feeding experiments in this study show that the irregular particle shape and fine particles of the raw polyetheretherketone powder lead to low powder mass flows and a high tendency to agglomeration during DED-LB/P processing. Due to the altered surface topography, heat-treating the polymer powder results in stable powder feeding conditions with a reproducibly adjustable powder mass flow. A multi-pass deposition strategy with a gentle energy input maintains process stability and prevents thermal decomposition of the polyetheretherketone powder in DED-LB/P. The absence of pores in the cross-sectional examination indicates that coatings with a high density can be deposited. Furthermore, the fabricated coatings exhibit a semi-crystalline structure and an excellent bond strength to the metallic substrate. In order to reduce the roughness of the coatings, an additional laser remelting step represents an appropriate process strategy. The characterization of the coated stainless steel 316L substrates shows that the DED-LB/P process has no decisive effect on the hardness, while the dimensional accuracy is slightly affected. Based on the polyetheretherketone coatings produced in this study, DED-LB/P with a thulium laser may have great potential for future medical applications because there is no need to add flow and absorbing additives to the polymer powde
Keywords: PEEK; Polyetheretherketone; Coating; Laser material processing; Directed energy deposition; Additive manufacturing

Generation of Polyamide 12 Coatings on Stainless Steel Substrates by Directed Energy Deposition with a Thulium-Doped Fiber Laser (DED-LB/P) - Wittmann, Alexander; Hentschel, Oliver; Sommereyns, Alexander; Schmidt, Michael (Polymers, 2022)
Due to their good material properties (e.g., corrosion and wear resistance, biocompatibility), thermoplastic materials like polyamide 12 (PA12) are interesting for functional coatings on metallic components. To ensure a spatially resolved coating and to shorten the process chain, directed energy deposition of polymer powders by means of a laser beam (DED-LB/P) offers a promising approach. Due to characteristic absorption bands, the use of a thulium fiber laser with a wavelength of 1.94 μm is investigated in a DED-LB/P setup to generate PA12 coatings on stainless steel substrates without the need to add any absorbing additives. The influence of the energy density and powder mass flow was analyzed by infrared thermography. Furthermore, the coatings were characterized by differential scanning calorimetry, laser-scanning-microscopy, optical microscopy and cross-cutting tests. The results in this study demonstrate for the first time the basic feasibility of an absorber-free DED-LB/P process by using a thulium fiber laser. PA12 coatings with a low porosity and good adhesion are achievable. Depending on the application-specific requirements, a trade-off must be made between the density and surface quality of the PA12 coatings. The use of infrared thermography is appropriate for in-situ detection of process instabilities caused by an excessive energy input.<br

Geometry‐Based Scan Curve Analysis: Rapid Method for the Evaluation of Scan Strategies in Powder Bed Fusion - Leupold, Simon; Willeke, Michael; Sommereyns, Alexander; Gehring, Matthias; Dineshbhai, Parmar Yankit; Stratmann, Nadine; Ziefuss, Anna Rosa; Kopp, Sebastian-Paul; Barcikowski, Stephan; Schmidt, Michael (Advanced Engineering Materials, 2025)
It is well known that scan strategies have an essential role in powder bed fusion (PBF). For the comparison of different scan strategies, however, it is usually necessary to evaluate manufactured samples or run simulations. Given the typically lengthy nature of these processes, this study focuses on finding a rapid preprocess evaluation method for scan strategies using geometrical approaches: line buffer-based calculations and a point density field. Both approaches only depend on the geometry of the scan strategy. While these calculations should apply to most PBF processes, this study uses the evaluation methods to predict the differences that four unique scanning strategies have in PBF of polymers using an near-infrared laser source. Polyamid 12 powder with Lanthanum hexaboride nanoparticles and a commercial black-dyed Polyamid 12 powder are used for processing. The calculation of the line buffer-based surface energies of these scanning strategies correctly predicted the sequence in which the scanning curve appeared to have received the laser energy. Moreover, the defects observed in the manufactured samples appear to be related to the variation in point density of the scanning strategies. These promising results are the first step towards new preprocess evaluation methods, leading to improved predictability of different scan strategie
Created from Fastlane, Scopus look-up
Keywords: additive manufacturing; numerical simulations; process characterizations; rapid evaluation methods; toolpath generation

How colloidal surface additivation of polyamide 12 powders with well-dispersed silver nanoparticles influences the crystallization already at low 0.01 vol% - Hupfeld, Tim; Sommereyns, Alexander; Schuffenhauer, Thomas; Zhuravlev, Evgeny; Krebs, Moritz; Gann, Stan; Keßler, Olaf; Schmidt, Michael; Gökce, Bilal; Barcikowski, Stephan (Additive Manufacturing, 2020)
As Additive Manufacturing (AM) is fast-growing, properties adaption of feedstock materials for AM is becoming more and more relevant due to high quality standards in industrial applications. Compared to traditional manufacturing techniques like injection molding, laser powder bed fusion (PBF-LB) of polymers has a very limited variety of processable materials, which is a major obstacle for future growth. Nanocomposites are an established material class for addressing the limitations in PBF-LB but often show poor dispersion of the nanomaterial in/on the polymer powder. Especially in the context of plasmonic nanomaterials and composites, where the state of aggregation considerably influences the optical properties, dispersion plays an important role. Our study presents a deeper understanding of the colloidal surface additivation of polyamide 12 (PA12) powders with laser-generated plasmonic silver nanoparticles, leading to high dispersion of the nanoparticles on the micropowder surface with good reproducibility. The additivation is ruled by colloidal stability and control of electrostatic forces between particles and resulted in powders that could successfully be processed on a PBF-LB machine to generate plasmonic-functionalized parts. Finally, we introduce the surface specific nanoparticle dose (surf%) as scaling key parameter complementary to the commonly used mass specific dose (wt%) to appropriately describe nanoparticle load, proving the effect of such surface additivation on the recrystallization behavior of PA12. Via flash calorimetry, already at 0.01 vol% silver load, significant nanoparticle-induced heterogeneous nucleation effects are evident, whereas the thermal properties analyzed by conventional calorimetry remain unaffected.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Electrostatic deposition; Fast scanning calorimetry (FSC); Laser ablation in liquid (LAL); Laser powder bed fusion (PBF-LB); Nanocomposite; Selective laser sintering (SLS); Surface functionalization

Influence of sub-monolayer quantities of carbon nanoparticles on the melting and crystallization behavior of polyamide 12 powders for additive manufacturing - Sommereyns, Alexander; Hupfeld, Tim; Gann, Stan; Wang, Tao; Wu, Cunchen; Zhuravlev, Evgeny; Lüddecke, Arne; Baumann, Stéphanie; Rudloff, Johannes; Lang, Marieluise; Goekce, Bilal; Barcikowski, Stephan; et al. (Materials & Design, 2021)
In this paper, the influence of 0.005 vol% and 0.05 vol% of carbon nanoparticles on the surface of polyamide 12 powder particles by dry coating and colloidal additivation is evaluated in great detail concerning thermal and microstructural properties. The dispersion of the nanoparticles on the polymer surface influences the flowability of the feedstock powder already during the additivation process. When analyzing the composite powders dynamically and isothermally with fast scanning and differential scanning calorimetry, carbon nanoparticles influence the crystallization behavior of the feedstock material significantly by acting as nucleation seeds, already at a few percent of a monolayer coating, while showing no effect on the fast heating process. The difference in calorimetric properties and crystallization behavior between the additivation methods of different abrasive forces is discussed. The surface-additivated carbon nanoparticles significantly increase the crystalline area by up to a threefold and the crystallization rate by up to a hundredfold. Furthermore, they change the crystal growth from a typical two- to three-dimensional growth of spherulites to a one- to two-dimensional growth of ellipsoidal impinged lamellar structures. Between 0.005 vol% and 0.05 vol% of well-dispersed carbon nanoparticles should be added to polyamide 12 to trigger an anisotropic heterogeneous nucleation while avoiding agglomerate
CRIS-Team Scopus Importer:2021-02-05
Keywords: Nanoparticle additivation; Laser ablation in liquids; Carbon nanocomposites; Calorimetry; Polymer crystallization

Laser-based coating process of PA12 on stainless steel substrates - Wittmann, Alexander; Hentschel, Oliver; Ermer, Jakob; Sommereyns, Alexander; Huber, Florian; Schmidt, Michael (Lasers in Manufacturing (LiM) 2021, 2021)

Light matters: Quantifiable optical interaction between near-infrared laser radiation and nano-additivated polymers in all states of matter present in laser powder bed fusion - Sommereyns, Alexander; Leupold, Simon; Rudlof, Frederic; Willeke, Michael; Ghosh, Anindya; Ohannessian, Ben; Merwin, Daniella; Elahi, Reza; Barcikowski, Stephan; Vogel, Nicolas; Schmidt, Michael (Additive Manufacturing, 2024)
Comprehending the interaction between light and material is crucial to the success of various laser-based processes, including laser powder bed fusion of polymers. The use of the promising near-infrared laser wavelength in laser powder bed fusion of polymers is limited by the need for absorption-enhancing (nano-) additives and insufficient knowledge of the (nano-) particulate impact on the material and process behavior. The presented study lays the groundwork for an improved understanding of the laser-material interaction at different states of matter in laser powder bed fusion by means of thermo-optical measurements with a double integrating sphere setup. The authors characterize polyamide 12 and its nanocomposite powder surface-coated with carbon black nanoparticles by two different additivation methods. The attenuation coefficient and penetration depth of each material were calculated based on the measured transmittance and reflectance in all relevant states of matter. The effects of the feedstock particle size, the nano-additivation method, and the nanoparticle quantity were evaluated. The optical results of resolidified samples were validated using a commercially available spectrophotometer. Finally, the authors were able to qualitatively correlate the thermo-optical results with the depth of fusion of specimens processed at 808 nm.<br
Keywords: laser powder bed fusion; polymer nanocomposite; thermo-optical property; near-infrared laser; attenuation coefficient

On the Mechanism and Productivity of Single-Pulse Laser Fragmentation of Organic Curcumin Dispersions in a Continuous Flat Jet Flow-Through Reactor - Friedenauer, Tina; Spellauge, Maximilian; Sommereyns, Alexander; Rehbock, Christoph; Huber, Heinz Paul; Barcikowski, Stephan (Journal of Physical Chemistry C, 2025)
Curcumin is a natural food additive (nutraceutical), whose bioavailability is impaired by low solubility, a drawback which may be overcome by particle size reduction. Microparticle (MP) laser fragmentation in liquids (LFL) is an emerging production method for sensitive, organic submicron particles (SMPs) and nanoparticles (NPs), as it is characterized by processing at minimal chemical degradation. However, the fragmentation mechanisms need to be understood to tune the MP-LFL process toward a high SMP yield. Therefore, we used pump-probe microscopy (PPM) to elucidate the dynamics of shockwave formation and cavitation bubble growth on single-curcumin particles in correlation with laser fluence utilizing a ps-pulsed laser at 1040 nm. We observed LFL to occur at a threshold fluence of 60 mJ cm–2. Furthermore, we found a pressure buildup of 308 MPa within the particle, which exceeds the material’s tensile strength by one order of magnitude, hinting at strong contributions of photomechanical effects during curcumin MP-LFL. Consecutively, we examined the transfer to MP dispersions where concentration effects during MP-LFL were studied using a ps-pulsed laser at 532 nm and an optimized continuous flat jet (FJ) reactor, which is characterized by the ability to process particularly high concentrations of up to 1000 mg L–1 due to the low liquid layer thickness. An increased mass yield of SMP and NP (determined by UV–vis extinction spectroscopy and SEM) was found at high educt concentrations of 500 mg L–1, which leads to a relative SMP mass yield of 62% and a productivity of 278 mg h–1, with the potential for quantitative conversion of all MPs into SMPs at optimized illumination conditions (100% yield, 500 mg h–1). The outstandingly low by-product fraction (< 0.5%) by far surpasses the standard comminution processes applied today, rendering the MP-LFL technology even more relevant to the food or pharma secto
Keywords: Bubbles; Dietary supplements; Fragmentation; Lasers; Liquids

Performance Comparison of Surface Sensitizers for Diode Laser Powder Bed Fusion of Polyamide 12 - Willeke, Michael; Sommereyns, Alexander; Leupold, Simon; Lüddecke, Arne; Kwade, Arno; Hantke, Nick; Sehrt, Jan T.; Schmidt, Michael; Ziefuss, Anna Rosa; Barcikowski, Stephan (Advanced Engineering Materials, 2025)
The efficient processing of polyamide 12 (PA12) in laser-based additive manufacturing with near-infrared (NIR) diode lasers requires modification with NIR-absorbing additives. This study presents the absorbance-normalized investigation, where the loading of copper sulfide (CuS), lanthanum hexaboride (LaB6), and carbon black (CB) on PA12 is adjusted to achieve identical absorbance at the diode laser printing wavelength of 808 nm. This approach enables a direct comparison of their effects on the processability, mechanical properties, and thermal stability, independent of the energy input. Interestingly, sub-vol% sensitizer amounts are sufficient for processing. CuS, at only 0.04 vol%, achieves the highest mechanical strength (≈41 MPa) of the printed parts, good powder flowability, and thermal stability. LaB6 achieves the best flowability, but requires three times higher loading, affecting fusion behavior, while CB needs increased amounts due to its low density. All nanoparticle-modified powders maintain stable optical properties during laser powder bed fusion processing, which is a basic requirement for a refresh rate of 0%, outperforming conventional organic dyes in thermal stability. These findings pave the way for high-performance polymer feedstocks in diode laser-based additive manufacturin

Quality over quantity: How different dispersion qualities of minute amounts of nano-additives affect material properties in powder bed fusion of polyamide 12 - Sommereyns, Alexander; Gann, Stan; Schmidt, Jochen; Chehreh, Abootorab Baqerzadeh; Luddecke, Arne; Walther, Frank; Goekce, Bilal; Barcikowski, Stephan; Schmidt, Michael (Materials, 2021)
The great interest, within the fields of research and industry, in enhancing the range and functionality of polymer powders for laser powder bed fusion (LB-PBF-P) increases the need for material modifications. To exploit the full potential of the additivation method of feedstock powders with nanoparticles, the influence of nanoparticles on the LB-PBF process and the material behavior must be understood. In this study, the impact of the quantity and dispersion quality of carbon nanoparticles deposited on polyamide 12 particles is investigated using tensile and cubic specimens manufactured under the same process conditions. The nano-additives are added through dry coating and colloidal deposition. The specimens are analyzed by tensile testing, differential scanning calorimetry, polarized light and electron microscopy, X-ray diffraction, infrared spectroscopy, and micro-computed tomography. The results show that minute amounts (0.005 vol%) of highly dispersed carbon nanoparticles shift the mechanical properties to higher ductility at the expense of tensile strength. Despite changes in crystallinity due to nano-additives, the crystalline phases of polyamide 12 are retained. Layer bonding and part densities strongly depend on the quantity and dispersion quality of the nanoparticles. Nanoparticle loadings for CO2 laser-operated PBF show only minor changes in material properties, while the potential is greater at lower laser wavelengths.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Additively manufactured parts; Dispersion; Laser powder bed fusion; LB-PBF; Mechanical properties; Nanocomposites; Nanoparticles; Polyamide 12

Roughly Spherical: Tailored PMMA-SiO2 Composite Supraparticles with Optimized Powder Flowability for Additive Manufacturing - Canziani, Herbert; Bever, Frederik; Sommereyns, Alexander; Schmidt, Michael; Vogel, Nicolas (ACS Applied Materials and Interfaces, 2021)
Particulate materials with well-engineered properties are of key importance for many aspects in our daily life. Polymer powders with high flowability, for example, play a crucial role in the emerging field of powder-based additive manufacturing processes. However, the polymer- and composite material selection for these technologies is still limited. Here, we demonstrate the design of spherical polymethyl methacrylate (PMMA) and PMMA-SiO2 composite supraparticle powders with excellent powder flowability and tailored composition for powder-based additive manufacturing. Our process assembles these powders from the bottom up and affords a precise control over surface roughness and internal morphology via the choice of colloidal primary particles. We establish process-structure-property relationships connecting external spray-drying parameters and primary particle sizes with the resulting supraparticle roughness and, subsequently, with the macroscopic powder flowability and powder bed density. In a second step, we demonstrate the control of composition and internal morphology of PMMA-SiO2 composite supraparticles based on different mass mixings and diameter ratios of the two primary particle dispersions. Finally, we successfully apply the prepared supraparticle powders in powder bed additive manufacturing. The optimized flowability of the composite powders allows the production of two-layered square specimens with fusion between the individual layers and a uniform and tunable distribution of nanoscale SiO2 additives without requiring the addition of any flowing aids.
Keywords: PMMA; additive manufacturing; composite powder; nanoscale; spray drying; supraparticles

Scaling up colloidal surface additivation of polymer powders for laser powder bed fusion - Hupfeld, Tim; Doñate-Buendía, Carlos; Krause, Matthias; Sommereyns, Alexander; Wegner, Andreas; Sinnemann, Thorsten; Schmidt, Michael; Gökce, Bilal; Barcikowski, Stephan (Procedia CIRP, 2020)
Nanoadditivation of polymer materials has high potential to meet the needs of material modification for laser powder bed fusion (PBF-LB/P), e.g. by tuning optical or mechanical properties. Colloidal additivation of polymer powders has proven to avoid aggregation of nanofillers on the polymer surface during additivation. In our study, we demonstrate kg-scale, continuous colloidal surface additivation of polymer powders to generate sufficient amounts for PBF-LB/P process development and manufacturing of test specimens. Furthermore, colloidal additivation achieves a high surface coverage even at low wt% and allows PBF-LB/P with CO2 and diode lasers to form parts preserving the superior nanoparticle dispersion within TPU and PA12.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Colloidal additivation; Deposition; Laser powder bed fusion (PBF-LB); Laser synthesis and processing of colloids; Nanocomposites; Selective laser sintering (SLS); Upscaling

Stack and Structure: Ultrafast Lasers for Additive Manufacturing of Thin Polymer Films for Medical Applications - Bartels, Dominic; Reg, Yvonne; Borandegi, Mahboobeh; Marschall, Maximilian; Sommereyns, Alexander; Schmidt, Michael (Journal of Manufacturing and Materials Processing, 2025)
Overcoming the limitations of powder-based additive manufacturing processes is a crucial aspect for the manufacturing of patient-specific sophisticated implants with tailored properties. Within this work, a novel manufacturing process for the fabrication of polymer-based implants is proposed. This manufacturing process is inspired by the laminated object manufacturing technology and is based on using thin films as raw material, which are processed using an ultrafast laser source. Utilizing thin films as a starting material helps to avoid powder contamination during additive manufacturing, thus supporting the generation of internal cavities that can be filled with secondary phases. Additionally, the use of medical materials mitigates the burden of a later certification of potential implants. Furthermore, the ultrafast laser supports the generation of highly resolved structures smaller than the average layer thickness (from 50 to 100 µm) through material ablation. These structures can be helpful to obtain progressive part properties or a targeted stress flow, as well as a specified release of secondary phases (e.g., hydrogels) upon load. Within this work, first investigations on the joining, cutting, and structuring of thin polymer films with layer thickness of between 50 and 100 µm using a ps-pulsed laser are reported. It is shown that thin film sizes of around 50 µm could be structured, joined, and cut successfully using ultrafast lasers emitting in the NIR spectral rang
Keywords: additive manufacturing; 3D printing; ultrafast laser; ultra-short-pulse additive manufacturing; laminated object manufacturing; polymer film

Thermo‐Optical Analysis of Surface‐ and Volume‐Additivated Polymer Powders for Near‐Infrared Laser Powder Bed Fusion - Sommereyns, Alexander; Schmidt, Jochen; Leong, Cheechau; Tischer, Florentin; Schmidt, Michael (Advanced Photonics Research, 2025)
Near-infrared laser sources have the potential to change the process dynamics in laser powder bed fusion of polymers. To take full advantage of the shorter processing laser wavelength, the addition of absorbing additives, such as carbon black nanoparticles, becomes inevitable. Many nanoparticle characteristics can influence the laser-material interaction, such as quantity, dispersion, and position relative to the polymer matrix, but have not been investigated under processing conditions. Therefore, this study improves the understanding of the optical material properties present in laser powder bed fusion by quantifying the thermo-optical properties of PA11 powder, melt and solid, additivated with minute amounts of carbon black nanoparticles on the surface and throughout the volume of the particles. Surface-additivation results in the highest increase in laser attenuation overall and creates a segregated network that acts as a barrier to laser penetration in the molten and solid state. By contrast, the random distribution of agglomerated nanoparticles throughout the particle volume allows most of the laser radiation to pass through. Other nanoparticle effects, such as thermal stabilization and crystal formation, affect the volume-additivated particles the most. The thermo-optical results are complemented by analysis of process-relevant powder, thermal, structural, and compositional material propertie
Keywords: attenuation coefficient; carbon black; dry coating; laser powder bed fusion; matrix incorporation; polymer nanocomposites; thermo-optical characterization